Malicious behaviour of node and its significant security techniques in MANET- a review - Khan, Burhan ul Islam; Olanrewaju, Rashidah Funke; Habaebi, Mohamed Hadi (INSI Publications, 2013)
Mobile adhoc network is one of the major discussed topic in the field of wireless network and communication system from past few decades. Various extensive research work conducted in the past shows that mobile adhoc network is shrouded with various type of issues e.g. dynamic topologies, inefficient routing policies, unwanted energy depletion, and security. Although various solutions has been explored for addressing other issues in MANET, but solutions previously introduced for mitigating security threats in MANET are yet to be standardized or found robust enough. One of the root causes for the same is that there is a tremendous amount of unpredictability in the behavior of the mobile nodes in MANET, be it regular node or erroneous node or malicious node. Hence, this paper discusses only the significant research work that has been introduced in the past for the purpose of mitigating security threats in MANET.